Fighting Over the Bangka Sea: The Tin Mining Conflict in the Marine Area of Bangka Regency - Aimie Sulaiman; La Ode Muhamad Muliawan; Komang Jaka Ferdian; Marwan Yaumal Akbar (Journal of Governance, 2023)
Abstract: The tin mining conflict in the marine area of Bangka Regency involves four main actors: the government and PT Timah as the spearhead of the tin exploitation, illegal miners, fishermen, and tourism businessmen. This research uses qualitative methods by collecting data through in-depth interviews and literature studies. This article found that economic factors are accounted for by the node that equalizes the motives of actors to be present in the socio-economic dynamics of the region. However, there are two different patterns of sea utilization, namely tin mining, which causes damage to 57.09% of coral reefs, reduces fishing hauls and threatens 16,000 traditional fishermen who depend on the sea for fishing, and the development of tourism, which requires the maintenance of marine ecosystems, on the other hand, it can cause conflict between actors. The unequal power network between actors causes the distribution of benefits over the sea in Bangka Regency to be unsatisfactory. The operationalization of state power through spatial arrangements in the form of mining business licenses has made the state the actor that receives the most economic benefits. Relations with state actors in the workings of the shadow state allow illegal miners to gain economic benefits because they can be connected to the global tin business chain. On the other hand, the combination of the lack of power, pseudo-participation in policy formation, and the stalemate of alternative participation has resulted in the marginalization of fishermen.